Anogenital distance in water buffalo females and relationship with reproductive performance. Preliminary results - Héctor Nava-Trujillo; Simón Zambrano-Salas; Justin Dijak; Adriana Morgado-Osorio; Quintino D’Andrea (Revista Científica)
Recently, anogenital distance (AGD) has been studied in cattle, and cows with shorter AGD have a better reproductive performance. There needs to be more information about AGD and its influence on reproductive performance in the case of water buffaloes. Therefore, the objectives of this preliminary study were to characterize the anogenital distance in water buffalo females and evaluate if this trait is related to reproductive performance. Data for this study was registered in a commercial farm in El Vigia, Merida, Venezuela, with crosses of Mediterranean x Murrah water buffalo breeds (Bubalus bubalis). The collected data from 171 females (26 nulliparous and 145 with at least one calving) included anogenital distance (millimeters), age (days), weight (kilograms), height at the withers (millimeters), and hip height (millimeters). The calving-to-conception interval (days) was registered from 88 females. Descriptive statistics and correlation analysis (Pearson’s correlation coefficient) were carried out between AGD, age, weight, wither height, and hip height. Water buffalo cows with at least one previous calving were categorized as short or long AGD based on the median AGD. The calving-to- conception interval was modeled against the AGD category using a variance analysis adjusted by parity and season of calving. All analyses were carried out with R studio version R4.2.2. The anogenital distance averaged 152±20.60 mm, and it was correlated positively with age (0.5516; p<0.05), weight (0.4574; p<0.05), height at the withers (0.4056, p<0.05), and hip height (0.3703; p<0.05). Water buffalo cows with at least one previous calving were categorized as short-AGD or long-AGD (short <157.0 mm> long), and as expected, the mean of AGD differed between groups (145.61 vs. 180.50 mm, respectively, p<0.05). It was observed that the calving-to- conception interval was shorter in water buffalo cows with short AGD (70.82 vs. 96.60 days, p<0.05). In conclusion, anogenital distance in water buffalo females positively correlates with age, weight, wither height, and hip height. Additionally, a long anogenital distance was associated with lower reproductive performance (longer calving-to-conception interval). This fact could be attributed to the adverse effects of prenatal exposure to androgens on reproductive organs and endocrine pathways; however, more research is needed to understand this better. This could be the first study establishing the relationship between anogenital distance and reproductive performance in Bubalus bubalis. However, considering the reduced number of animals and observations, testing, and validating these findings with a bigger population is necessary. In the same direction, there is a need to carry out more research to clarify the mechanism involved in improving reproductive performance and the heritability of AGD.